Larvicide Effects of Serratia marcescens strain MBC1 Extract on Instar III Larvae of Aedes aegyti - Lestari, Mutia Dinda; Nukmal, Nismah; Setyaningrum, Endah; Farisi, Salman; Arifiyanto, Achmad (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2022)
Bakteri merupakan kandidat yang berpotensi sebagai larvasida Aedes aegypti. Penelitian ini bertujuan untuk mengetahui pengaruh ekstrak Serratia marcecsens strain MBC1 terhadap kematian larva instar III Aedes aegypti. Penelitian ini merupakan penelitian eksperimental dengan dua macam bentuk pengujian, yaitu uji larvasida untuk menentukan mortalitas dan uji lanjut untuk melihat perkembangan larva setelah perlakuan larvasida. Larva instar III diberi perlakuan dengan konsentrasi 125, 250, 500, dan 1.000 ppm. Uji larvasida diamati selama 24-72 jam. Uji lanjut larva instar III diberi perlakuan dengan konsentrasi 500 dan 1.000 ppm serta diamati sampai semua larva mati. Kontrol positif menggunakan Abate® 1% dan kontrol negatif menggunakan air sumur. Hasil analisis probit didapatkan bahwa nilai LC50 dan LC90 ekstrak S. marcescens adalah 66.426,02 dan 749.001,41ppm. Larva instar III mati pada 18 hari setelah perlakuan ekstrak S. marcescens strain MBC1. Hasil dari penelitian ini menunjukkan bahwa larvasida ekstrak S. marcescens mempengaruhi lamanya siklus hidup dan mati sebelum mencapai stadium dewasa. Bacteria have potencial as larvicide of Aedes aegypti. The purpose of this study is to determine the effect of Serratia marcescens strain MBC1 against larval third instars of Aedes aegypti. This research was an experimental study with two kinds of testing. The larvicide test to determine the mortality of the larval and the continuous test to observe the development of the larval after treatment with the larvacide. The third instars of mosquito larval were given bacterial extract in four concentrations (125, 250, 500, and 1000 ppm), and observed mortality during 72 hours. The continuous larvicide test was observed at two concentrations (500 and 1,000 ppm). The observation is completed when all of the larvae died. The positive control used Abate® 1% and the negative control used natural water. The treatment was repeated 4 times. The results show that LC50 and LC90 of S. marcescens extract are 66,426.02 dan 749,001.41 ppm. All of the larvae in the continuous test die after 18 days have been givenan extract of S. marcescens strain MBC1. The experiment shows that the larvicide of extract of S. marcescens influences the length of the life cycle and larvae of Ae. aegypti die before reaching the adult.